Edukasi Pencegahan Kebakaran dan Penanganan Luka Bakar Melalui Sekolah Perempuan Permata Siaga - Oktaviani, Dwi Putri; Larasati, Adhisti Sophia; Nursyafaat, Anastia; Taqiyya, Azizah Vella; Sunita, Elni; Septiani, Indri; Iriani, Nitha Putri; Nurlatifah, Novie; Ananda, Rahmatika; Nurhidayat, Reski; Nida, Shoffatun; Salsabila, Syifa; Putri, Tegar Wulandari; Ramdhaniati, Thusiani; Prakhasa, Zivanka Aurelia Sheva; Mirwanti, Ristina (Politeknik Negeri Jember, 2026)
Fire is one of the non-natural calamities that frequently occurs at the household level and has the potential to cause burn injuries with serious health impacts. Hegarmanah Village is considered an area with high vulnerability to fire incidents, which highlights the importance of education to improve community knowledge and preparedness. This activity aimed to educate village women on fire prevention and burn management through the Permata Siaga Women’s School program. The methods applied included interactive lectures, hands-on practice, and evaluation using pre-test and post-test. The program was attended by 15 female participants with diverse ages and educational backgrounds. The results showed a significant notable rise in knowledge and skills, as indicated by the rise in the average score from the pre-test to the post-test. Participants were also able to correctly practice the use of fire extinguishers and implement proper first aid procedures for burn injuries. In conclusion, this educational program was effective in enhancing women’s preparedness in facing fire risks and managing burn injuries in household settings.